The Application of Green Architecture Concepts in the Design of Integrated MTsN And MAN in Sabang - Deviani, Fitri; Aini, Qurratul (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2024)
The city of Sabang, which is in Pulau Weh, Aceh Province, for now does not have an integrated secondary school yet, this causes many children to choose schools outside the city of Sabang. The city of Sabang needs an integrated secondary school at the MTsN and MAN levels with proper facilities in terms of innovatively supporting good education for the community. The site location of object design (the Integrated MTsN and MAN) located on Jalan Ie Meulee, Sukajaya, City of Sabang, Aceh. The chosen design approach is Green Architecture, with emphasis on ”working with climate”, it means buildings must be designed to work with the climate and natural resources. Through this approach, buildings are designed to adapt to their environment by utilizing natural conditions, climate and the surrounding environment that are applied to the design. The analysis used in this design is functional analysis, site analysis, building analysis. Based on the stipulation of the Ministry of Education and Culture, the Integrated MTsN and MAN buildings are planned according to their position at the Municipal level, so this school is designed as a type B school. The land area for the Design of Integrated MTsN and MAN in Sabang City is 2.5 Ha. This design has several mass buildings with a range of 2-3 stories high. Based on the 2012-203 RTRW of Sabang City Settlement and Urban Infrastructure Development Strategy (SPPIP), the Ground Coverage Area (KDB) is 60% (15,000 m²) and the Floor Area ratio (KLB) is 1.2 (18,000 m²). The facilities in this design are classrooms, teachers' rooms, principal and school committee rooms, sports fields, canteens, prayer rooms and other supporting facilities.